Impact of diethyl carbonate in PVA based gel polymer electrolytes on dye-sensitized solar cells performance - Aziz, M. F.; Mohd Abid, Mohd Asyadi Azam; Mohd Noor, Ikhwan Syafiq; Buraidah, Mohd Hamdi; Mohd Arof, Abdul Kariem (Springer, 2021)
In this report, the potential of diethyl carbonate (DEC) as a plasticizer infuence the conductivity and dye-sensitized solar cells (DSSCs) efciency. PVA-PC-EC-DMSO-TBAI-KIDEC based gel polymer electrolytes (GPEs) have been prepared and utilized in DSSCs. The GPEs contain DEC have been characterized using X-ray difraction and electrical impedance spectroscopy (EIS). X-ray difraction indicates the amorphousness of the prepared GPEs. The highest conductivity derived from the EIS measurement is (6.64±0.07) mS cm−1 exhibited GPE containing 5.47 wt.% PVA: 10.95 wt.% PC: 8.21 wt.% EC: 60.22 wt.% DMSO: 8.05 wt.% TBAI: 3.45 wt.% KI: 1.08 wt.% I2: 2.57 wt.% DEC gel polymer electrolyte. The highest conducting electrolyte was dominated by the highest charge carrier mobility and difusivity. The conductivity-temperature plotted is Arrhenius. The DSSCs with the highest conducting GPE exhibits the highest efciency of 7.50%. Other parameters are short-current density (Jsc) of 16.05 mA cm−2, open-circuit voltage (Voc) of 0.64 V and fll factor (FF) of 0.73. In short, the DEC plasticizer improves the conductivity and DSSCs efciency precisely